Technology for Small Sewage Treatment: The Chinese Perspective: A Review - Wu, Xiaoyun; Zheng, Youfei; Lin, Kesi; Bing, Mao (Asian Journal of Chemistry, 2014)
On the basis of demographic projections, it is estimated that the quantity of sewage which will be produced in China between 2009 and 2015 will increase from 35.52 billion tons to 56.65 billion tons. Sewage treatment and its management is one of the most critical environmental issues of today. The treatment and disposal of sewage contribute a considerable proportion of the cost. The increasing amount of sewage and more and more legislative regulation of its disposal have stimulated the need for efficient and economical technologies to process sewage. Currently, the predominant method for the disposal of this sewage is biological treatment. The small sewage treatment facilities are cost-effective and getting benefit instantly. Here we review the state of knowledge and technology in small sewage treatment, which makes proposals to the construction of sewage treatment.